Video-assisted thoracoscopic lung biopsy in children - Oak S; Akhtar T; Viswanath N; Pathak R (Wolters Kluwer Medknow Publications, 2006)
Minimal invasive surgical techniques have gained high acceptance in thoracic surgery during the last 10 years. Video-assisted thoracoscopy (VATS) is less invasive than open thoracotomy and its development is associated with expansion of indication for lung biopsies. Lung biopsy remains an important investigation in the diagnosis of few of the lung disorders despite improved diagnostic yield of high resolution computed tomography scanning. Thoracoscopic lung biopsy is becoming the procedure of first choice for the diagnosis of many localized and diffuse lung diseases. We report a small series of eight patients who underwent VATS lung biopsy to demonstrate the safety and efficacy of this procedure.